Measurement of performance-service indicators of KLIA transit - Rosli, Nur Shazwani; Kadar Hamsa, Abdul Azeez (2013)

(untitled)
1. Objective With the rise in the provision of several public transit systems, Kuala Lumpur is still seen as one of the lowest public transport passenger usages in Asia, mainly because of increasing number of private car ownership. The modal split ratio between the use of private and public transport in Kuala Lumpur is 84: 16. The focus of this paper is to evaluate the KLIA transit service performances through measurement of service indicators such as passenger ridership, service frequency, connectivity, and service quality. The perceptions of users on the existing performance of the KLIA transit are crucial to determine the level of service which is currently offered by the operators/agencies and the service which require improvement to further increase the passenger ridership. 2. Data/Methodology The evaluation of transit service performances was made by using revealed preference approach. It is considered imperative to ascertain what indicators affect the use of transit services among the private vehicle dominant community. About 100 questionnaires were distributed at two important stations namely KL Sentral and Putrajaya stations. The methods of analysis applied include univariate, bivariate, and RII (Relative Importance Index). The relationship between service indicators and use of KLIA transit services were established by using bivariate analysis method. Relative Importance Index (RII) method was applied to establish the ranking of the service characteristics (the most important, second most important etc.) of the transit performance as perceived by the users. 3. Results/Findings The major findings indicated that most of the users who were using KLIA transit were federal government employees working at Putrajaya, the new federal government administrative centre. The findings on service indicators influencing KLIA transit use indicate “time savings” and “train connectivity” were considered as the most favourable factors in attracting the users. On the other hand, most of the users were found dissatisfied with the fare charged, frequency of services provided and waiting time before boarding the transit. 4. Implications for Research/Policy The findings indicated the importance of service indicators in attracting choice riders to use public transportation especially for work purposes. The consistent performances of providing better quality services including less waiting time, affordable fare, good connectivity and improved frequency are very vital to increase the passenger ridership of public transportation system especially in a private vehicle dominant society such as in Kuala Lumpur, Malaysia.